2020
DOI: 10.1186/s40478-020-0892-2
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of DNA mismatch repair enzyme immunohistochemistry as a screening test for hypermutated gliomas

Abstract: A subset of gliomas has DNA repair defects that lead to hypermutated genomes. While such tumors are resistant to alkylating chemotherapies, they may also express more mutant neoantigens on their cell surfaces, and thus be more responsive to immunotherapies. A fast, inexpensive method of screening for hypermutated gliomas would therefore be of great clinical value. Since immunohistochemistry (IHC) for the DNA mismatch repair (MMR) proteins Msh2, Msh6, Mlh1, and Pms2 is already used to screen for hypermutated co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 33 publications
3
34
0
Order By: Relevance
“…Indeed, Hodges et al [ 3 ] demonstrated that immunohistochemical loss of at least one MMR protein expression was associated with the hypermutation profile in glioma patients. This correlation was confirmed in further recent studies [ 4 , 5 , 6 ]. Immune checkpoint inhibitors, in particular Nivolumab and Pembrolizumab (anti PD-1), were tested in several types of tumors with MMR deficiency (MMRd), showing impressive antitumor activity [ 7 , 8 , 9 , 10 , 11 , 12 ]; based on these results, the FDA approved the use of pembrolizumab in patients with any solid tumor with MMRd after progression from prior chemotherapy [ 13 ].…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Indeed, Hodges et al [ 3 ] demonstrated that immunohistochemical loss of at least one MMR protein expression was associated with the hypermutation profile in glioma patients. This correlation was confirmed in further recent studies [ 4 , 5 , 6 ]. Immune checkpoint inhibitors, in particular Nivolumab and Pembrolizumab (anti PD-1), were tested in several types of tumors with MMR deficiency (MMRd), showing impressive antitumor activity [ 7 , 8 , 9 , 10 , 11 , 12 ]; based on these results, the FDA approved the use of pembrolizumab in patients with any solid tumor with MMRd after progression from prior chemotherapy [ 13 ].…”
Section: Introductionsupporting
confidence: 87%
“…In particular, the presence of mutated IDH can affect epigenetic alterations and lead to a higher probability of alteration of MMR protein expression in grade 3 gliomas. Moreover, immunohistochemical loss of MMR protein expression may be useful to detect hypermutated cancers as demonstrated by McCord et al [ 6 ]; in this study, the authors showed that IHC loss of MMR proteins can detect hypermutated gliomas with high sensitivity and specificity; yet, in this study, 9 out of 100 gliomas were hypermutated and 8 out of 9 had complete loss of expression of at least one MMR protein. All hypermutated patients had previously received temozolomide.…”
Section: Discussionmentioning
confidence: 59%
“…The association between MMR status and hypermutation is still unclear in gliomas [ 6 , 8 , 18 ]. The high frequency of hypermutated gliomas in our cohort, which is much higher than the 3.5% previously reported in glioblastoma [ 5 ], may suggest that the immunohistochemical loss of MMR proteins is useful to detect hypermutated tumors, as recently proposed by McCord et al [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association between MMR status and hypermutation is still unclear in gliomas [ 6 , 8 , 18 ]. The high frequency of hypermutated gliomas in our cohort, which is much higher than the 3.5% previously reported in glioblastoma [ 5 ], may suggest that the immunohistochemical loss of MMR proteins is useful to detect hypermutated tumors, as recently proposed by McCord et al [ 8 ]. Although 8/9 hypermutated gliomas in McCord et al [ 8 ] had MMR immunohistochemical loss and MMR mutations, MSI status was not explored and whether hypermutated gliomas identified by means of MMR immunohistochemical loss are responsive to immune check point inhibitors remained unsolved.…”
Section: Discussionmentioning
confidence: 99%
“…Promoter methylation-mediated silencing of MGMT is associated with increased sensitivity towards temozolomide and present in the vast majority of IDH-mutant gliomas [ 19 ]. A fraction of recurrent IDH-mutant gliomas develops resistance against TMZ by acquiring mutations in MMR genes, leading secondarily to a hypermutated genotype [ 10 , 13 , 36 , 44 , 47 ].…”
Section: Introductionmentioning
confidence: 99%